Pembelajaran Seni Kaligrafi Berbasis Eksperimen Kimia di Sekolah Dasar Negeri 8 Kawunglarang Rancah Kabupaten Ciamis - Sopiah, Siti (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Learning the art of calligraphy based on chemical experiments is an activity of learning the art of calligraphy in developing the potential of students to foster creativity, instill value, and develop productive abilities by using harmless materials, namely using colored plants. The purpose of this research was to determine the process and to obtain calligraphy work in learning the art of calligraphy based on chemical experiments. The type of method used in this research is field qualitative research. The data sources in this study were divided into two: first, primary data sources consisting of the principal, educators, and students of SDN 8 Kawunglarang Rancah; second, secondary data sources obtained through tracing of various references. Furthermore, the data collection instruments used were observation, interviews, and documentation, as well as the data analysis techniques used, namely through three stages including data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of learning the art of calligraphy based on chemical experiments includes the planning, implementation, and evaluation stages. The work of SDN 8 Kawunglarang students is still in the basic stages so there are several mistakes in its making.